2013
DOI: 10.9790/3008-0562732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fenitrothion on some histo-architecture of freshwater fish Channa punctatus

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Likewise, mild to severe necrosis, pyknosis, shrinkage of renal tubules, ruptured renal corpuscle, ruptured collecting duct, haemorrhage, etc. were recorded in the kidney (Akhter & Saha 2013;Al-Emran et al 2018;Kabir et al 2019). Sloughing of superficial epidermal cells, uneven intestinal folding and physically damaged intestinal villi have been observed (Ahmed et al 2016).…”
Section: Histopathology Of Different Organsmentioning
confidence: 97%
See 3 more Smart Citations
“…Likewise, mild to severe necrosis, pyknosis, shrinkage of renal tubules, ruptured renal corpuscle, ruptured collecting duct, haemorrhage, etc. were recorded in the kidney (Akhter & Saha 2013;Al-Emran et al 2018;Kabir et al 2019). Sloughing of superficial epidermal cells, uneven intestinal folding and physically damaged intestinal villi have been observed (Ahmed et al 2016).…”
Section: Histopathology Of Different Organsmentioning
confidence: 97%
“…Likewise, mild to severe necrosis, pyknosis, shrinkage of renal tubules, ruptured renal corpuscle, ruptured collecting duct, haemorrhage, etc. were recorded in the kidney (Akhter & Saha 2013; Al‐Emran et al . 2018; Kabir et al .…”
Section: Impacts Of Sumithion On the Physiology Of Adult Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…in striped gourami, Trichogaster fasciata (Hasan et al, 2021). Moreover, numerous studies revealed toxicities of different pesticides in various tissues of fish includes sumithion to Nile tilapia, Oreochromis niloticus (Kabir et al, 2019), Thai sharputi, Barbonymus gonionitus (Al-Emran et al, 2018), common carp (Hossain et al, 2016); fenitrothion to spotted snakehead, Channa punctatus (Akhter and Saha, 2013); cypermethrin to amazon bluespotted corydora Corydoras melanistius (Santos et al, 2012). Pesticides also altered the hemato-biochemical profiles of fish (Sivanatarajan and Sivaramakrishnan, 2013).…”
Section: Effects Of Pesticides On Fishmentioning
confidence: 99%